Fatores de proteção para doença periodontal e impacto da condição periodontal na qualidade de vida de pacientes em hemodiálise: um estudo de coorte - Leal, Paula Miliana (2023)
Introduction: Periodontal diseases are common in patients with end-stage renal disease and can impact their quality of life. In this sense, it is important to identify the factors that may interfere with the periodontal condition and, consequently, with the quality of life of patients undergoing hemodialysis. Objective: To evaluate changes in the periodontal condition of patients on hemodialysis and to verify the impact of the periodontal condition on their quality of life. Methodology: This is a longitudinal study of the prospective cohort type that was carried out with 226 patients undergoing hemodialysis treatment in two hospitals in the city of Campina Grande-PB. The patients underwent an initial assessment in 2016 and in 2019 they were reassessed. Periodontal condition was determined using the modified Community Periodontal Index (CPI). Patients answered a socioeconomic and demographic questionnaire and the Oral Health Impact Profile-14 (OHIP-14) questionnaire was used to assess oral health-related quality of life (QHRSB). Descriptive and multivariate statistical analysis was performed using Decision Tree Analysis using the CHAID (Chi-squared Automatic Interaction Detector) algorithm. Results: The decision tree revealed that improvement in periodontal condition was associated with education (p-value = 0.012), age group (p-value = 0.006), marital status (p-value = 0.002) and diabetes (p-value = 0.002). = 0.010), and that the impact on QHRSB can be explained by self-reported color (p-value = 0.039) and reported use or not of dental floss (p-value = 0.028). Conclusion: The results suggest that having a higher level of education, being younger than 60 years old, being married or living in a stable relationship and not having diabetes were protective factors for reducing the rate of gingival bleeding and that self-declared white and not flossing may influence QHRSB in hemodialysis patients.